Fuzzy Logic Based DTC Control of Synchronous Reluctance Motor - Madbouly, Sayed O. (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
This paper presents the utilization of a fuzzy logic controller (FLC) within the speed control loop of the direct torque control (DTC) algorithm. The aim is to enhance the dynamic performance of a 3-phase synchronous reluctance motor (SynRM) in variable speed applications. The proposed FLC employs the speed error and change of speed error to generate the torque command signal needed for the torque hysteresis comparator within the DTC scheme. The system being analyzed comprises of a synchronous reluctance motor, voltage source converter and the proposed fuzzy logic-based DTC. In order to evaluate the performance of the proposed controller, a comprehensive system model is developed and simulated using MATLAB Simulink. The dynamic response of the entire system is investigated when subjected to various command speeds and loading conditions. It is found that the proposed controller achieves fast and precise dynamic response under all operating conditions. Furthermore, a comparative analysis is conducted between utilizing the FLC and the traditional proportional integral differential (PID) controller in the speed control loop of the DTC, the results demonstrate a significant improvement in the dynamic response when employing FLC compared to the traditional PID controller.